Historiography of Falsafa in Post-Qajar Iran: Its History and Classification - Amin-Beidokhti, Hanif (Die Welt des Islams, 2026)
The historiography of falsafa in Persian as a genre of philosophical literature is a young phenomenon, rooted in the encounter of the Iranian philosophical community with modern European philosophy. European historiography of philosophy as a discipline is itself modern and was initiated in the eighteenth century and evolved thereafter with the historiography of falsafa as its by-product. Despite its relative youth, Persian historiography of falsafa has yielded considerable outcomes. This paper outlines the historical trajectory leading to the emergence of this new genre of philosophical literature in Iran. It then provides a classification of these works and highlights their salient features. This body of literature offers insights not only for philosophers but also for scholars of cultural studies, social sciences, and political sciences, given that Persian historiographies, like their European counterparts, have also been employed to endorse political or religious identities through the construction of nativist or non-nativist grand narratives.